2007
DOI: 10.1128/iai.01375-06
|View full text |Cite
|
Sign up to set email alerts
|

An Increase in Epithelial Cell Apoptosis Is Associated with Chronic Intestinal Nematode Infection

Abstract: It is well established that homeostasis of the intestinal epithelium becomes dysregulated during gastrointestinal helminth infection and is under immune control. An increase in both enterocyte proliferation and the subsequent generation of crypt hyperplasia are hallmarks of chronic infection with Trichuris muris, a large intestinal dwelling nematode. The effect of this parasitic infection on apoptosis induction in the large intestine and its regulation has been neglected. To address this, mice of resistant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 56 publications
(57 reference statements)
2
37
0
Order By: Relevance
“…Even though ST has been shown to induce apoptosis in enterocytes (43,64), the increased mitotic events and Paneth cell numbers appear to reflect rather an increased turnover rate of the small-intestinal epithelium (26). This is in agreement with Cliffe et al, who reported on crypt hyperplasia accompanied by increased apoptosis of enterocytes in chronic infection of mice with the nematode Trichuris muris (13).…”
Section: Discussionsupporting
confidence: 82%
“…Even though ST has been shown to induce apoptosis in enterocytes (43,64), the increased mitotic events and Paneth cell numbers appear to reflect rather an increased turnover rate of the small-intestinal epithelium (26). This is in agreement with Cliffe et al, who reported on crypt hyperplasia accompanied by increased apoptosis of enterocytes in chronic infection of mice with the nematode Trichuris muris (13).…”
Section: Discussionsupporting
confidence: 82%
“…Total RNA from epithelial cells was isolated with the use of the previously described method 27 . cDNA was generated with the use of an IMPROM-RT kit (Promega) and Absolute QPCR SYBR Green (ABgene Epsom, Surrey, United Kingdom) was used for quantitative PCR.…”
Section: Supplementary Methodsmentioning
confidence: 99%
“…Trichuris muris is a natural counterpart nematode that dwells in the large intestine of mice (2,3). This parasite is very similar to the human parasite, and its larvae also embed in the epithelium of the cecum, causing alterations in the homeostasis of the epithelium as well as epithelial cell hyperplasia (3,4). Different strains of mice respond to T. muris infection differently depending on the type of immune response mounted.…”
mentioning
confidence: 99%